Suboxic DOM is bioavailable to surface prokaryotes in a simulated overturn of an oxygen minimum zone, Devil’s Hole, Bermuda - Parsons, Rachel J.; Liu, Shuting; Longnecker, Krista; Yongblah, Kevin; Johnson, Carys; Bolaños, Luis M.; Comstock, Jacqueline; Opalk, Keri; Kido Soule, Melissa C.; Garley, Rebecca; Carlson, Craig A.; Temperton, Ben; et al. (Frontiers in Microbiology, 2023)
Oxygen minimum zones (OMZs) are expanding due to increased sea surface temperatures, subsequent increased oxygen demand through respiration, reduced oxygen solubility, and thermal stratification driven in part by anthropogenic climate change. Devil's Hole, Bermuda is a model ecosystem to study OMZ microbial biogeochemistry because the formation and subsequent overturn of the suboxic zone occur annually. During thermally driven stratification, suboxic conditions develop, and organic matter and nutrients accumulate at depth. In this study, the bioavailability of the accumulated dissolved organic carbon (DOC) and the microbial community response to reoxygenation of suboxic waters was assessed using a simulated overturn experiment. The surface inoculated prokaryotic community responded to the deep (formerly suboxic) 0.2µm filtrate with cell densities increasing 2.5-fold over 6 days while removing 5µmol L -1 of DOC in this treatment. After 12 days, the surface community began to shift, and DOC quality seemingly became less diagenetically altered along with an increase in SAR202, a Chloroflexi that can degrade recalcitrant dissolved organic matter (DOM). Labile DOC production after 12 days coincided with an increase of Nitrosopumilales, a chemoautotrophic ammonia oxidizing archaea (AOA) that converts ammonia to nitrite based on the ammonia monooxygenase (amoA) gene copy number and nutrient data. In comparison, the inoculation of the deep anaerobic prokaryotic community into surface 0.2µm filtrate demonstrated a die-off of 25.5% of the initial inoculum community followed by a 1.5-fold increase in cell densities over 6 days in this treatment. Within 2 days, the prokaryotic community shifted from a Chlorobiales dominated assemblage to a surface-like heterotrophic community devoid of Chlorobiales. The DOM quality changed to less diagenetically altered material and coincided with an increase in the ribulose-1,5-bisphosphate carboxylase/oxygenase form I (cbbL) gene abundance followed by an influx of labile DOM. Overall, upon reoxygenation, the deep DOM that accumulated under suboxic conditions is bioavailable to surface prokaryotes that utilize the accumulated DOC initially before switching to a community that can both produce labile DOM via chemoautotrophy and degrade the more recalcitrant DOM.